The Medina Embolic Device: Karolinska experience. Issue 1 (February 2018) - Bhogal, P; Brouwer, PA; Yeo, L; Svensson, M; Söderman, M
Background: The aim of this study was to report our single centre experience with the Medina Embolic Device (MED). Methods: We performed a retrospective analysis of prospectively collected data to identify all patients treated with the MED. A total of 14 aneurysms (non-consecutive), in 13 patients, were treated including one ruptured and one partially thrombosed aneurysm. Fundus diameter was ≥5 mm in all cases. We evaluated the angiographic appearances, the clinical status, complications, and the need for adjunctive devices or repeat treatments. Results: Aneurysm location was cavernous internal carotid artery (ICA; n  = 1), supraclinoid ICA ( n  = 1), terminal ICA ( n  = 2), anterior communicating artery (AComA; n  = 4), A2–3 ( n  = 1), M1–2 junction ( n  = 1), posterior communicating artery (PComA; n  = 1), superior cerebellar artery (SCA; n = 1), and basilar tip ( n  = 2). The average aneurysm fundus size was 8.6 mm (range 7–10 mm) and average neck size 3.75 mm (range 1.9–6.9 mm). Immediate angiographic results were modified Raymond–Roy occlusion classification (mRRC) I n  = 2, mRRC II n  = 1, mRRC IIIa n  = 2, mRRC IIIb n  = 2, the remaining 7 aneurysms showed complete opacification. At follow-up angiography (mean 5 months) mRRC I n  = 5, mRRC II n  = 5, mRRC IIIa n = 3, and persistent filling was seen in 1 aneurysm. Overall, four patients had repeat treatment and one is pending further treatment. Of the aneurysms treated with more than one MED, 75% showed complete occlusion at 6-month follow up whereas only one aneurysm treated with a single device showed complete occlusion. Overall, three patients had temporary complications and there were no deaths. Conclusions: The MED is an intra-saccular flow-diverting device with satisfactory angiographic results and an acceptable safety profile. Use of a single MED cannot be recommended and further longer term studies are needed prior to widespread clinical use.